Hybrid Chelator-Based PSMA Radiopharmaceuticals: Translational Approach - Hanane Lahnif (MDPI AG, 2021)
(1) Background: Prostate-specific membrane antigen (PSMA) has been extensively studied in the last decade. It became a promising biological target in the diagnosis and therapy of PSMA-expressing cancer diseases. Although there are several radiolabeled PSMA inhibitors available, the search for new compounds with improved pharmacokinetic properties and simplified synthesis is still ongoing. In this study, we developed PSMA ligands with two different hybrid chelators and a modified linker. Both compounds have displayed a promising pharmacokinetic profile. (2) Methods: DATA5m.SA.KuE and AAZTA5.SA.KuE were synthesized. DATA5m.SA.KuE was labeled with gallium-68 and radiochemical yields of various amounts of precursor at different temperatures were determined. Complex stability in phosphate-buffered saline (PBS) and human serum (HS) was examined at 37 °C. Binding affinity and internalization ratio were determined in in vitro assays using PSMA-positive LNCaP cells. Tumor accumulation and biodistribution were evaluated in vivo and ex vivo using an LNCaP Balb/c nude mouse model. All experiments were conducted with PSMA-11 as reference. (3) Results: DATA5m.SA.KuE was synthesized successfully. AAZTA5.SA.KuE was synthesized and labeled according to the literature. Radiolabeling of DATA5m.SA.KuE with gallium-68 was performed in ammonium acetate buffer (1 M, pH 5.5). High radiochemical yields (>98%) were obtained with 5 nmol at 70 °C, 15 nmol at 50 °C, and 60 nmol (50 µg) at room temperature. [68Ga]Ga-DATA5m.SA.KuE was stable in human serum as well as in PBS after 120 min. PSMA binding affinities of AAZTA5.SA.KuE and DATA5m.SA.KuE were in the nanomolar range. PSMA-specific internalization ratio was comparable to PSMA-11. In vivo and ex vivo studies of [177Lu]Lu-AAZTA5.SA.KuE, [44Sc]Sc-AAZTA5.SA.KuE and [68Ga]Ga-DATA5m.SA.KuE displayed specific accumulation in the tumor along with fast clearance and reduced off-target uptake. (4) Conclusions: Both KuE-conjugates showed promising properties especially in vivo allowing for translational theranostic use.